(3eUGOQ GdONd GdeJYOOs - (3Cdjf(B, (3QhHjQJ Ls ((3GdQjGV(B:s (3ecJHI GdYHjcGf(B,s, 2005)
(3eGd Sgd(B- (3edjhfjQ GdYTQ ObGFb(B-(3UjZI TLQI GdfbO(B-(3GdSdSdI GdLHdjI(B- (3GSJQGJjLjGJ GdCSge GdahQjI(B-(3GQHM cKjQG aj GdYbGQ(B- (3KQhI aj MLR GdQgf hGdJfGRd(B-(3GdMUhd Ydi CQHGM VNeI (B- (3OaY VQGFH GdCTNGU GdBNQjf(B-(3CMOK BdI ddfbhO(B- (3fTQ GdeYdheGJ hJMdjdgG(B- (3GdJMhd GdSQjY ddedcjIs
Keywords: (3GdCQHGMs; (3GdCehGds; (3GdESJKeGQs; (3eUGOQ GdONds